Concepts of Modern Physics - Arthur Beiser, Shobith Mahajan, S Rai Choudhary (New Delhi MedTech Science Press, 2024)
School of Mathematics and Natural Science
MIR No.: 196
Order Date: 2024-10-16
Order No: CU/OPEX/LIBRARY/41/2024-25
Received Date: 2024-10-30
Keywords: Physics, Modern Physics